A Communication-less adaptive protection scheme for Self-Healing distribution systems. (June 2023) - Wong, JunYing; Tan, ChiaKwang; Rahim, N.A.; Tan, Rodney H.G.
Highlights: Communicative protection schemes pose economic and security issues. Existing communicative-less schemes focus on microgrid protection. No comms-less schemes on overcurrent protection for self-healing systems. Fault location estimates and relay load flows to predict relay settings. Relay setting group selected locally by artificial neural network. Abstract: Network reconfiguration has allowed supply restoration to disrupted areas after fault events. However, changes in network topology can alter the direction and magnitude of fault currents and jeopardize the coordination of overcurrent relays. Adaptive protection schemes using system-wide communications have been developed to solve this issue by performing dynamic relay recalibration. Unfortunately, system-wide communications are also associated with huge economic costs, data integrity issues, and limitations of infrastructures. Moreover, in less developed communities, such schemes are less applicable. Although various communication-less schemes have been proposed, they mainly focused on adapting overcurrent relay protection for different distributed generation penetrations and microgrid islanding statuses. Currently, no communications-less adaptive protection method has been proposed to address the miscoordination of protection relays caused by network reconfiguration for supply restoration. Thus, this paper presents a communication-less adaptive protection scheme to maintain relay coordination in a reconfigurable distribution network that performs supply restoration. The scheme deploys microcontroller units to predict the correct relay settings by monitoring load flows through the relays. The scheme is demonstrated on the IEEE 33-bus and 69-bus test distribution systems using two different relay placement strategies, non-directional and directional relays. The proposed scheme achieved up to 10.8 times lower disruptions than the existing system in N-1–1 contingency scenarios. Overall, the scheme provides a simple and low-cost alternative to improve the effectiveness of power system protection in a reconfigurable network. © 2017 Elsevier Inc. All rights reserved.